STUDIES ON EXPERIMENTAL INFECTION WITH ASPERGILLUS FUMIGATUS IN OSTRICH CHICKS - A. M. Hereba; M. S. Shathele; M. A.Hamouda2 (Journal of Animal and Plant Sciences, 2016)
This work was aimed to study Aspergillus fumigatusinfection(alone or preceded by immunosuppresive agents) in ostrich chicks. The birds (n=15) were randomly divided into three groups of 5 ostrich, each: The birds in the group (1) were inoculated intratracheally with 5 ml of A. fumigatus inoculums (2.7x106 spores/ml). The birds in the group (2) received three dexamethasone injections (2 mg/kg intramuscularly every 48h) preceding to the intratracheal inoculation with 5 ml of A. fumigatusinoculums (2.7x106 spores/ml). The birds in the group(3) were kept as control and were inoculated with only 5 ml of suspending media. After one week post infection, the birds in the group(II) showed cough, anorexia, dyspnea and weight loss. On radiograph the chest showed diffuse hazy infiltrates with a fine nodular appearance. At necropsy, multifocal white nodules were seen distributed on the surfaces of the air sacs and throughout the lung lobes. Histologically, multifocal necrotic, granuloma were seen with central radiating septated and branching hyphae of Aspergillusfumigatusin the lungs and liver.To our knowledge, it is a first time for experimental induction of Aspergillus fumigatus infection in ostrich. It is also concluded that the diagnosis of the disease in the ostrich is quite similar to other avian species including a thorough history, clinical signs, radiography and histologic demonstration of the organism
Keywords: A. fumigatus; ostrich; histopathology